Development of an Interactive Canva–Smart Board to Improve Indonesian Language Learning Outcomes in Elementary Schools - Raini Febrianti; Yusrizal Yusrizal; Ilham Nazaruddin (cendekia citra gemilang, 2026)
This study aimed to develop an interactive learning media based on Canva and Smart Board that is valid, practical, and effective in improving elementary students’ Indonesian language learning outcomes. The research employed a Research and Development (R&D) method using the 4D development model, consisting of the Define, Design, Develop, and Disseminate stages. The participants were 26 fifth-grade students of SD Negeri 050585 Tanjung Jati. Data were collected using material expert validation sheets, media expert validation sheets, student response questionnaires, and learning achievement tests in the form of pretests and posttests. The results indicated that the developed media achieved an average validation score of 3.85 from the material expert and 3.88 from the media expert, both categorized as highly valid. Student responses reached 100% in the “very good” category, indicating that the media was highly practical for classroom implementation. The effectiveness of the media was demonstrated by the improvement in students’ average scores from 38.46 on the pretest to 92.30 on the posttest. Furthermore, the N-Gain score of 0.87 was classified as high, indicating that the media was highly effective in enhancing students’ learning outcomes. Therefore, the Canva–Smart Board interactive media is considered valid, practical, and effective for improving Indonesian language learning outcomes in elementary schools